Factors Related To The Use Of Long-Term Contraception Method Woman Of Fertile Couple In Sialang Munggu Village The Work Area Community Health Centers Sidomulyo 2020 - Alyensi, Fatiyani; Alwinda, Thara Widadari (JURNAL IBU DAN ANAK, 2020)
One of the objectives of the national mid-term development plan of 2015-2019 is by increasing the use of MKJP and RPJNM 2019-2023 is prioritize population and family planning. The purpose of this study was to determine the factors associated with the use of long-term contraceptive methods. This research was conducted at Sialang Munggu Village, public health centers Sidomulyo in August 2019 until Maret 2020. This type of research is descriptive analytic, cross sectional approach. The population were all of contraception acceptors Sialang Munggu village in 2018. The sample were 99 people, used Quota sampling. This research used quisionaire instrument and analyze used chi square test. The result showed that there is a relationship between husband support and the use of MKJP (). There is a relationship between attitude and the use of MKJP (). There is a relationship between the completeness of service KB and the use of MKJP ().